ANALISIS SENTIMEN TERHADAP PROGRAM MERDEKA BELAJAR-KAMPUS MERDEKA (MBKM) PADA TWITTER MENGGUNAKAN ALGORITMA NAIVE BAYES CLASSIFIER - Irawansyah, Rody Safri; Irfan A, Lalu A. Syamsul; Wiriasto, Giri Wahyu (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2023)
Merdeka Belajar-Kampus Merdeka (MBKM) is a policy of the Indonesian Ministry of Education and Culture, which plays an important role in autonomous and flexible learning in student learning activities outside of study programs. However, MBKM has pros and cons, so it is necessary to analyze and evaluate its policies to improve performance through feedback from the community. This research will conduct a sentiment analysis on the MBKM policy on Twitter user tweets from 2022 with the keywords